Evaluation of pig body weight variation, amino acid levels, and distillers dried grains with solubles on pig performance - Tolosa Russi, Andres Fernando (Kansas State University, 2022)
The 3 chapters of this thesis involve 1) a meta-analysis of pig body weight (BW) variation from birth to market, 2) a study evaluating reducing digestible lysine (Lys) and tryptophan to lysine ratio (Trp:Lys) in the diet for pigs as a nutritional strategy to slow down pig growth due to the COVID-19 pandemic, and 3) a study evaluating growth performance of pigs fed a diet with or without distillers dried grains with solubles (DDGS) with increased digestible threonine (Thr). Chapter 1 describes a meta-analysis of the literature to develop prediction equations for coefficient of variation (CV) and standard deviation (SD) as a function of pig BW from birth to market. The results indicate that there is a quadratic decreasing relationship between the CV of the population and pig BW, where the slope of decrease becomes smaller as mean pig BW increases from birth to market. A quadratic increase for the relationship is also observed for SD, in which the slop becomes smaller as pig mean BW increases from birth to market. Chapter 2 describes an experiment that aimed to slow-down pig growth during the COVID-19 pandemic, due to processing plant shutdowns, by decreasing standardized ileal digestible (SID) Lys and SID Trp:Lys ratio in the diet. The results of this study indicate that reducing SID Lys from 100 to 80% of the pigs’ requirement and formulating diets with 16% SID Trp:Lys during the grow-finish period decreased growth performance and feed efficiency, and consequently, final BW was reduced by 8.6 and 11.7 kg after 119 days of consuming the reduced SID Lys or SID Trp:Lys diet, respectively. Chapter 3 utilized 2,160 pigs to determine if increasing SID Thr:Lys in the diet is needed to optimize the growth performance of grow-finish pigs when DDGS is also included in the diet. The results indicate that pigs fed a diet with DDGS had reduced growth performance regardless of the level of digestible Thr in the diet. This study used DDGS, which is a source of insoluble fiber, therefore, different results may occur if a soluble fiber source is provided.
Keywords: Variation; Lysine; Tryptophan; Threonine; DDGS; Pig